2018
DOI: 10.1080/21691401.2018.1468770
|View full text |Cite
|
Sign up to set email alerts
|

The combinational effect of E6/E7 siRNA and anti-miR-182 on apoptosis induction in HPV16-positive cervical cells

Abstract: In the present research, we assumed that reducing the amounts of E6 and E7 oncoproteins by a specific siRNA sequence and recovering p53 and RB proteins, along with the recovery of the FOXO1 protein by applying anti-miR-182, would increase apoptosis and reduce proliferation rate in cancer cells. The HPV16-positive CaSki cervical cancer cell line was used. 48 hours after transfection of siRNA for targeting E6 and E7 oncoproteins and anti-miR-182, expression of its cellular targets p53, p21 and FOXO1 was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Cervical cancer is one of the most common cancers and the second leading cause of cancer-related death in women worldwide [1,2], with 274,000 deaths annually [3], which is also a complex disease involving the abnormal expression of many oncogenes and tumour suppressor genes [4]. The discovery of novel therapeutics requires a comprehensive understanding of the disease biology.…”
Section: Introductionmentioning
confidence: 99%
“…Cervical cancer is one of the most common cancers and the second leading cause of cancer-related death in women worldwide [1,2], with 274,000 deaths annually [3], which is also a complex disease involving the abnormal expression of many oncogenes and tumour suppressor genes [4]. The discovery of novel therapeutics requires a comprehensive understanding of the disease biology.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, H. Javadi et al during a study on CaSki cancer cells showed that following combination therapy with E6-siRNA and cisplatin, the cells’ sensitivity to cisplatin and subsequent induction of apoptosis increases [ 19 ]. In the current study, the results of the MTT assay were also confirmed by flow cytometry assay with Annexin V/PI staining.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies evidence a controversy on the possible role of FOXO1 in cervical cancer, since its overexpression has been associated with a poor prognosis [ 57 ]. Moreover, it has been shown that the inhibition of the expression of E6 and E7 in Ca Ski cells recovers the expression of FOXO1, leading to apoptosis and to a reduction in the proliferation of cancer cells [ 58 ]. Interestingly, our RNAseq data showed a decrease in FOXO1 expression of −0.49 and −0.41 log2FC in cells with E6 and E7, respectively ( Tables S2 and S3 ).…”
Section: Discussionmentioning
confidence: 99%